2023
DOI: 10.1177/00222437231187630
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Versus Relevant Ads: How Creative Ads Affect Purchase Intention for New Products

Abstract: Creative ads are applied widely in new product marketing. The present research explores the impact of creative ads (divergent vs. relevant ads) on purchase intention for really new products (RNPs) and incrementally new products (INPs). A series of studies conclude that (a) divergent ads are more effective for promoting INPs; (b) relevant ads are more effective for promoting RNPs; (c) self-referencing mediates the joint effect of creative ads and product newness on purchase intention; and (d) there is an invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Conversely, the present study extended prior research by investigating how social exclusion influences RNP and INP adoption intentions. In addition, previous studies on new product adoption intention have also mainly focused on product characteristics (Fuerst et al, 2023; Kovalenko et al, 2022), individual traits (Herzenstein et al, 2007; Ma et al, 2014; Seyed Esfahani & Reynolds, 2021), and the marketing context (Jiang et al, 2023a; Wang et al, 2023; Zhang & Gong, 2022). Our study confirmed that, within an individual's social relationship, new product adoption can be affected by social exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, the present study extended prior research by investigating how social exclusion influences RNP and INP adoption intentions. In addition, previous studies on new product adoption intention have also mainly focused on product characteristics (Fuerst et al, 2023; Kovalenko et al, 2022), individual traits (Herzenstein et al, 2007; Ma et al, 2014; Seyed Esfahani & Reynolds, 2021), and the marketing context (Jiang et al, 2023a; Wang et al, 2023; Zhang & Gong, 2022). Our study confirmed that, within an individual's social relationship, new product adoption can be affected by social exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers generally purchase RNPs to display their individuality and portray a unique image by adopting the latest products (Luo et al, 2016). In contrast, INPs are improvements and enhancements of existing products involving no technical or market disruption, such as new phone models or new software versions (Jiang et al, 2023a). The newness of such products provides improved product features, functions, and experiences rather than new functional experiences (Fuchs & Diamantopoulos, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations